Silent sitting: a cross-curricular tool to promote resilience - Taplin, Margaret (International journal of children's spirituality, 2011)
Even though most teachers believe that it is important to help students to develop personal attributes such as resilience so they can cope with the challenges and changes of contemporary society, teachers and students are too often caught up with curriculum and exam pressures to be able to do very much about the development of personal values. Consequently we need to find a way to help teachers to address this need without abdicating their obligation to complete curricula and achieve results. The Sathya Sai Education in Human Values model is one such way, having been used successfully worldwide to support young people to develop resilience physically, mentally, emotionally and especially spiritually. One of many techniques that support this process is called ‘silent sitting’. This paper reports research data collected during a series of action research projects in two provinces in Mainland China that illustrate how teachers were able to increase their students’ intrapersonal resilience through spending just a few minutes several times a week in silent sitting. Interviews with children revealed some encouraging signs that they perceived silent sitting to have helped them to be more resilient, especially in their school work.